2021
DOI: 10.1038/s41371-021-00490-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ambulatory blood pressure monitoring profile on cognitive and imaging findings of cerebral small-vessel disease in older adults with cognitive complaints

Abstract: We investigated ambulatory blood pressure (BP) monitoring (ABPM) profiles and magnetic resonance imaging (MRI) findings of cerebral small-vessel disease (cSVD) in older adults with cognitive complaints who were grouped as follows: subjective cognitive decline, mild cognitive impairment, and dementia of Alzheimer’s type. Group comparisons and correlation analyses among demographic characteristics, cognitive and MRI findings, and ABPM profiles were performed. Furthermore, multivariate logistic regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, the increase of 24-h ambulatory blood pressure variability was associated with lower cognitive function in elderly hypertension with well-controlled blood pressure (59). Higher daytime systolic blood pressure was associated with a 3.73 risk of dementia and a 10.54 risk of MRI finding of subcortical vascular dementia (60). All these data highlight the need for the early management of these risk factors, particularly the blood pressure, even in the absence of clinical hypertension to prevent the risk of cognitive decline typically associated with aging.…”
Section: Health Factorsmentioning
confidence: 92%
“…Furthermore, the increase of 24-h ambulatory blood pressure variability was associated with lower cognitive function in elderly hypertension with well-controlled blood pressure (59). Higher daytime systolic blood pressure was associated with a 3.73 risk of dementia and a 10.54 risk of MRI finding of subcortical vascular dementia (60). All these data highlight the need for the early management of these risk factors, particularly the blood pressure, even in the absence of clinical hypertension to prevent the risk of cognitive decline typically associated with aging.…”
Section: Health Factorsmentioning
confidence: 92%
“…Eighteen studies (fifteen cross-sectional and three cohort studies) examined the risk of abnormal cognitive function among dipping groups in four thousand nine hundred and fifty-five patients (mean age 72.8 ± 9.1) [ 25 27 , 44 57 ]. Ten studies reported on 2918 patients (mean age 65.6 ± 11.2) global function neuropsychological tests stratified by dipping patterns [ 40 , 47 , 49 , 53 , 58 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cani et al examined the incidence of supine hypertension in a cohort of patients with idiopathic autonomic failure (IAF) [ 66 ]. Eight studies did not comment on hypertension history status of their population cohort [ 25 , 27 , 46 , 51 , 52 , 60 , 62 , 67 ] while five [ 25 , 27 , 51 , 52 , 67 ] of them stated that some patients received antihypertensive treatment. Guo and Ohya et al reported that none of the patients included received any antihypertensive treatment [ 46 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding BP and dementia risk, population-based studies showed that, from midlife to the geriatric stage, hypertension is correlated with future dementia, including both AD and VaD [100][101][102][103][104][105][106][107][108][109][110]. Another large review comprising 17 different systemic reviews concluded that hypertension leads to a higher risk of VaD and cognitive decline but to less AD [111].…”
Section: The Association Between Bp and Cognitionmentioning
confidence: 99%